2022
DOI: 10.1177/17588359221075495
|View full text |Cite
|
Sign up to set email alerts
|

A population-based study in resected esophageal or gastroesophageal junction cancer aligned with CheckMate 577

Abstract: Background: Results of CheckMate 577 show an improved disease-free survival for patients with resected esophageal or gastroesophageal junction cancer treated with adjuvant nivolumab compared with placebo (22.4 versus 11.0 months). Population-based data can provide insights in outcomes from clinical practice. The aim of our study was to investigate disease-free and overall survival in a nationwide population aligned with the inclusion criteria of CheckMate 577. Patients and Methods: Resected patients with stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
1
8
1
Order By: Relevance
“…21 For example, patients with PIC may more effectively benefit from adjuvant chemotherapy with anti-PD-L1 antibody. 52 This study has some limitations. In the clinical setting, a relatively small number of patients were included in this study, and the study was also retrospective in nature.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…21 For example, patients with PIC may more effectively benefit from adjuvant chemotherapy with anti-PD-L1 antibody. 52 This study has some limitations. In the clinical setting, a relatively small number of patients were included in this study, and the study was also retrospective in nature.…”
Section: Discussionmentioning
confidence: 91%
“…Thus, we believe that targeting PD‐L1 + MDSCs induced by infection may be an effective treatment strategy in patients with PIC 21 . For example, patients with PIC may more effectively benefit from adjuvant chemotherapy with anti‐PD‐L1 antibody 52 …”
Section: Discussionmentioning
confidence: 99%
“…However, some scholars have questioned the apparently shorter DFS time observed in the placebo group of CheckMate 577. A retrospective study in the Netherlands collected esophageal patients meeting the inclusion criteria of CheckMate 577 but not receiving adjuvant Nivolumab, revealing a median DFS of 19.7 months, which was much longer than that in placebo population of CheckMate 577 ( 58 ). It is also noteworthy that ESCC accounted for only 29% of participants in CheckMate 577, and no DFS benefit was observed in the Asian population or Asia region subgroup ( 42 ).…”
Section: Clinical Trials Testing the Combination Of Radiotherapy With...mentioning
confidence: 99%
“…62 In the CheckMate-577 study (the world's first phase III study of postoperative adjuvant therapy for ECs), improved disease-free survival was observed. 20,63 In the Attraction-02 and Attraction-03 clinical trials, immunotherapy was further proven to bring significant clinical benefits. In the ATTRACTION-3 trial, nivolumab significantly improved the OS compared with chemotherapy (median OS 10.9 vs. 8.4 months) in the treatment of ESCC.…”
Section: Current Clinical Trials Of Icis In Ecsmentioning
confidence: 99%
“…The ORR of pembrolizumab in combination with chemotherapy was 45.0% in the KEYNOTE‐590 study 62 . In the CheckMate‐577 study (the world's first phase III study of postoperative adjuvant therapy for ECs), improved disease‐free survival was observed 20,63 . In the Attraction‐02 and Attraction‐03 clinical trials, immunotherapy was further proven to bring significant clinical benefits.…”
Section: Introductionmentioning
confidence: 99%